2012
DOI: 10.1016/j.displa.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Reading e-books on a near-to-eye display: Comparison between a small-sized multimedia display and a hard copy

Abstract: Eighty-seven participants read an e-book either from a near-to-eye display, a small-size display or a hard copy. Eyestrain, visually induced motion sickness, changes in visual functioning, user experience, and the essential optical parameters of the reading equipment were evaluated. The results indicate that reading from a hard copy was the most comfortable experience. All near-to-eye displays induced eyestrain and sickness symptoms, but the magnitude of these symptoms varied according to the device. The adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 63 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…The e-books also are facing some challenges. Pölönen et al [27] demonstrate that reading from a hard copy was more comfortable than reading from e-books. Woody et al [28] also find that students do not prefer ebooks for depth study.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…The e-books also are facing some challenges. Pölönen et al [27] demonstrate that reading from a hard copy was more comfortable than reading from e-books. Woody et al [28] also find that students do not prefer ebooks for depth study.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Studies have reported some advantages of reading print materials: Having a sense of physical touch when reading print books (Evans, 2017; Loh & Sun, 2019; Mizrachi et al, 2018), focusing and remembering what you read better (Mangen et al, 2019; Mizrachi et al, 2018), facing no problems due to technological problems such as lack of power (Farinosi et al, 2016), encountering no risk of eye strain resulting from prolonged reading on the screen (Polonen et al, 2012) and the lack of distractions from digital tools (Smyth & Carlin, 2012). However, the dynamic nature of literacy today encompasses more than constructing meaning from printed texts.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the products provide a fixed display position, such as top‐right (Google‐Glass), lower‐right (Recon Jet‐Glasses), and center (Atheer Lab‐Glasses) of eyes. However, several studies investigated the visual ergonomics and postures in using NEDs for various tasks, 1,2,7–11 in its general perspective. Some of the results suggested that the experience with NEDs has been pleasing and the symptoms were as low as the larger displays.…”
Section: Introductionmentioning
confidence: 99%